Knowee
Questions
Features
Study Tools

Let a⃗ =3iˆ+jˆ−2kˆ,b⃗ =4iˆ+jˆ+7kˆ and c→=iˆ−3jˆ+4kˆ be three vectors. If a vectors p→ satisfies p→×b→=c→×b→ and p→⋅a→=0, then p→⋅(iˆ−jˆ−kˆ) is equal to

Question

Let \vec{a} = 3\hat{i} + \hat{j} - 2\hat{k}, \quad \vec{b} = 4\hat{i} + \hat{j} + 7\hat{k} \quad \text{and} \quad \vec{c} = \hat{i} - 3\hat{j} + 4\hat{k} \quad \text{be three vectors.} \newline If \( \vec{p} satisfies p×b=c×bandpa=0,thenp(i^j^k^)is equal to \vec{p} \times \vec{b} = \vec{c} \times \vec{b} \quad \text{and} \quad \vec{p} \cdot \vec{a} = 0, \quad \text{then} \quad \vec{p} \cdot (\hat{i} - \hat{j} - \hat{k}) \quad \text{is equal to}

...expand
🧐 Not the exact question you are looking for?Go ask a question

Solution

The problem involves vector operations, specifically cross product and dot product. Here are the steps to solve it:

Step 1: Given that p→×b→=c→×b→, we can say that p→ and c→ are in the same direction because the cross product of two vectors is another vector that is perpendicular to the plane containing the two original vectors. Therefore, we can write p→ = λc→, where λ is a scalar.

Step 2: We also know that p→⋅a→=0. Substituting p→ = λc→ into this equation, we get λc→⋅a→=0.

Step 3: Now, we can calculate c→⋅a→. c→ = iˆ−3jˆ+4kˆ and a→ = 3iˆ+jˆ−2kˆ. So, c→⋅a→ = (13) + (-31) + (4*-2) = 3 - 3 - 8 = -8.

Step 4: Substituting c→⋅a→ = -8 into λc→⋅a→=0, we get λ*(-8) = 0. Solving for λ, we find that λ = 0.

Step 5: Substituting λ = 0 into p→ = λc→, we find that p→ = 0.

Step 6: Finally, we need to find p→⋅(iˆ−jˆ−kˆ). Since p→ = 0, the dot product of p→ and any vector will be 0. Therefore, p→⋅(iˆ−jˆ−kˆ) = 0.

This problem has been solved

Similar Questions

Let  ,  and  be three given vectors. If  is a vector such that  and  then  is equal to

The cross product of two vectors A and B is another vectorGroup of answer choicesTrueFalse

Let a⃗ =3iˆ+jˆ−2kˆ,b⃗ =4iˆ+jˆ+7kˆ and c→=iˆ−3jˆ+4kˆ be three vectors. If a vectors p→ satisfies p→×b→=c→×b→ and p→⋅a→=0, then p→⋅(iˆ−jˆ−kˆ) is equal to

If three points are collinear, they are also coplanar.A.TrueB.FalseSUBMITarrow_backPREVIOUS

Let a=[−3,0,−3]𝑎=[−3,0,−3], b=[0,−1,0]𝑏=[0,−1,0], and c=[0,3,−2]𝑐=[0,3,−2]. Compute (a×b)⋅c(𝑎×𝑏)⋅𝑐.

1/1

Upgrade your grade with Knowee

Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.